2021
DOI: 10.1136/bmjopen-2021-050786
|View full text |Cite
|
Sign up to set email alerts
|

Acute subdural haematoma in the elderly: to operate or not to operate? A systematic review and meta-analysis of outcomes following surgery

Abstract: ObjectivesAcute subdural haematoma (ASDH) is a devastating pathology commonly found on CT brain scans of patients with traumatic brain injury. The role of surgical intervention in the elderly has been increasingly questioned due to its associated morbidity and mortality. Therefore, a systematic review and meta-analysis of the literature to quantify the mortality and functional outcomes associated with surgical management of ASDH in the elderly was performed.Design/settingA multidatabase literature search betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Insufficient stratification of these subpopulation groups has contributed to conflicting conclusions across studies, making it is difficult to develop a consensus of opinion or treatment guidelines. This is particularly relevant for the advanced geriatric population with acute SDHs where a call for guidelines regarding the role for surgery and possible rationing of care has been made [ 9 , 13 ]. With an anticipated surge in both the age and number of patients with SDHs requiring evacuation, the need for more accurate and reliable outcome reporting becomes greater each year [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient stratification of these subpopulation groups has contributed to conflicting conclusions across studies, making it is difficult to develop a consensus of opinion or treatment guidelines. This is particularly relevant for the advanced geriatric population with acute SDHs where a call for guidelines regarding the role for surgery and possible rationing of care has been made [ 9 , 13 ]. With an anticipated surge in both the age and number of patients with SDHs requiring evacuation, the need for more accurate and reliable outcome reporting becomes greater each year [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates have ranged from 40 to 90% for acute SDHs in select populations though more recent reports since 2010 have ranged from 15 to 67.2% for elderly patients [ 8 12 ]. Admittedly, there will always be some variation between studies, but such extreme differences have led to contradictory recommendations in the literature and underscore a greater issue at hand [ 10 , 13 15 ]. In this investigation, we sought to elucidate upon the unique subpopulations being combined in the current conventional reporting of SDHs and proposed a stratification system to help standardize and improve reproducibility of future research on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…However, survival and good functional outcome remain poor in many elderly patients, despite an aggressive treatment [ 14 , 15 , 16 , 17 ]. Therefore, in this age range, the treatment of choice is still debated and the object of ongoing trials [ 6 , 7 ], and most neurosurgeons prefer an initial conservative treatment, opting for surgery only in the case of an impaired state of consciousness. Although, while surgery has also been shown to have a major life-saving role in these patients when presenting with a severe clinical status, several studies have reported a high rate of poor functional outcome both at discharge and at 6 months follow-up, often due to the higher incidence of perioperative complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic ASDH in elderly patients is generally associated with a poor outcome [ 2 , 3 ]. Current guidelines on optimal treatment of these patients are based on weak evidences and, despite being considered a life-saving procedure, the role of surgery remains debated [ 4 , 5 , 6 , 7 , 8 ]. Thus, in these patients, it is quite common among clinicians preferring, at first glance, a conservative treatment, and shift toward surgery only in the case of deterioration in the state of consciousness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For each patient, we retrieved the age, sex, Charlson Comorbidity Index (CCI), history of arterial hypertension, use of antithrombotic drugs, the need for an urgent coagulopathy correction at A&E admission, mechanism of injury, neurological status measured by the Glasgow Coma Scale (GCS) at admission and during the entire preoperative period, pupillary size and light reaction, neurological deficits, and seizures. Patients were divided in three GCS level groups, both at arrival and soon before surgery: mild (13)(14)(15), moderate (9)(10)(11)(12), and severe (3)(4)(5)(6)(7)(8).…”
Section: Clinical and Radiological Data Collectionmentioning
confidence: 99%